2013
DOI: 10.1021/jp408017v
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Atomic Ordering Differences in Group 11 Nanosized Metals and Binary Alloy Catalysts by Resonant High-Energy X-ray Diffraction and Computer Simulations

Abstract: Resonant high-energy X-ray diffraction coupled to atomic pair distribution function analysis and computer simulations is used to study the atomic-scale structure of group 11 nanosized metals and binary alloy catalysts. We find that nanosized Cu is quite disordered structurally whereas nanosized Ag and especially Au exhibit a very good degree of crystallinity. We resolve Cu−Cu and Ag−Ag atomic correlations from Auinvolving ones in Au−Cu and Au−Ag nanoalloys and show that depending on the synthetic route group 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…This was explained by the occurrence of surface stress and lower repulsive forces between the atoms in smaller particles. Ristig et al., Petkov et al., Girao et al., and Bozzolo et al . all found a negative deviation from Vegard's law for AgAu nanoalloys.…”
Section: Resultsmentioning
confidence: 95%
“…This was explained by the occurrence of surface stress and lower repulsive forces between the atoms in smaller particles. Ristig et al., Petkov et al., Girao et al., and Bozzolo et al . all found a negative deviation from Vegard's law for AgAu nanoalloys.…”
Section: Resultsmentioning
confidence: 95%
“…It has been repeatedly shown that, thanks to the property of Fourier transformation, atomic PDFs derived from diffuse diffraction patterns of NPs show several distinct peaks allowing convenient testing and refinement of atomic-level models for NPs, including metallic ones. 12,[36][37][38] Experimental atomic PDFs G(r) derived from single XRD patterns for Ru core-Pt shell NPs and pure Ru cores collected using x-rays with energy of 78.070 keV, which is 325 eV below the Experimental atomic PDFs G(r) for Ru core-Pt shell and Pt-Ru alloy NPs derived from respective sets of two distinct XRD patterns, one collected using x-rays with energy of 78.070 8 keV and the other collected using x-rays with energy of 78.370 keV, are shown in Figure 3a.…”
Section: Resultsmentioning
confidence: 99%
“…However, unlike EXAFS, it shows these correlations up to the longest interatomic distance to which they can extend. 18,[35][36][37] Here we probed the K absorption edge of Pt species (78.395 keV; see Figure S3a) not only because of their particular importance to the catalytic properties of Ru-Pt NPs but also for obtaining diffraction data effectively "highlighting" the Pt-based and "dimming" the Ru-based components of the NPs. [24][25][26][27][28][29][30][31] The latter was critical to determining the 3D atomic arrangement at the interfaces between these components, as described below.…”
mentioning
confidence: 99%
“…The phase transition from a random alloy to a chemically ordered alloy type structure is oen accompanied by a shrinking of the distances between the metal atoms. 78 The HE-XRD/PDF results for PtIrCo/C, PtIr/C and PtCo/C catalysts treated from 400 and 800 C ( Fig. 3A and B) showed clear differences in crystallinity in terms of the sharpness of the peaks.…”
Section: Structural Characteristicsmentioning
confidence: 93%